Does it matter which citation tool is used to compare the h-index of a group of highly cited researchers? - Farhadi, Hadi; Salehi, Hadi; Yunus, Melor Md; Chadegani, Arezoo Aghaei; Farhadi, Maryam; Fooladi, Masood; Ebrahim, Nader Ale (American-Eurasian Network for Scientific Information, Jordan, 2013)
h-index retrieved by citation indexes (Scopus, Google scholar, and Web of Science) is used to measure the scientific performance and the research impact studies based on the number of publications and citations of a scientist. It also is easily available and may be used for performance measures of scientists, and for recruitment decisions. The aim of this study is to investigate the difference between the outputs and results from these three citation databases namely Scopus, Google Scholar, and Web of Science based upon the h-index of a group of highly cited researchers (Nobel Prize winner scientist). The purposive sampling method was adopted to collect the required data. The results showed that there is a significant difference in the h-index between three citation indexes of Scopus, Google scholar, and Web of Science; the Google scholar h-index was more than the h-index in two other databases. It was also concluded that there is a significant positive relationship between h-indices based on Google scholar and Scopus. The citation indexes of Scopus, Google scholar, and Web of Science may be useful for evaluating h-index of scientists but they have some limitations as well.